2014
DOI: 10.1002/marc.201400401
|View full text |Cite
|
Sign up to set email alerts
|

Poly(isobutylene) Nanoparticles via Cationic Polymerization in Nonaqueous Emulsions

Abstract: The preparation of poly(isobutylene) (PIB) nanoparticles via cationic emulsion polymerization is presented. As a requirement, an oil-in-perfluoroalkane nonaqueous emulsion is developed, which is inert under the carbocationic polymerization conditions. To stabilize the dichloromethane/hexane droplets in the fluorinated, continuous phase, an amphiphilic block copolymer emulsifier is prepared containing PIB and 1H,1H-perfluoroalkylated poly(pentafluorostyrene) blocks. This system allows for the polymerization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…For example, a nonaqueous emulsion polymerization system in perfluoroalkane-in-oil emulsion has been developed by Schuster et al to polymerize isobutylene. 169 M n 's of over 20 000 g/mol were achieved and it was suggested that the system could be applied also for the polymerization of 2-oxazolines or epoxides.…”
Section: Ionic Polymerizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a nonaqueous emulsion polymerization system in perfluoroalkane-in-oil emulsion has been developed by Schuster et al to polymerize isobutylene. 169 M n 's of over 20 000 g/mol were achieved and it was suggested that the system could be applied also for the polymerization of 2-oxazolines or epoxides.…”
Section: Ionic Polymerizationsmentioning
confidence: 99%
“…To circumvent the use of water but still benefit from a disperse system, reactions in organic emulsion could be envisioned. For example, a nonaqueous emulsion polymerization system in perfluoroalkane-in-oil emulsion has been developed by Schuster et al to polymerize isobutylene …”
Section: Reactions At the (Droplet) Interfacementioning
confidence: 99%
“…A brief explanation of silicon and silicone nomenclature is given in the Supporting Information. Figure and Table provide scaled comparisons between the chemical structures and physical properties, respectively, of PDMS and its closest carbon-based analogue, poly­(isobutylene) (PIB). A cursory glance at both of these polymer structures reveals marked differences. First, the Si–O bonds (1.63 Å) and Si–C bonds (1.90 Å) are much longer than the C–C bonds in PIB (1.53 Å).…”
Section: Introductionmentioning
confidence: 99%